Equity-based financing and risk in Islamic banks: A cross-country analysis - Hasan Mukhibad; Prabowo Yudo Jayanto; Risanda Alirastra Budiantoro; Bayu Bagas Hapsoro; Aas Nurasyiah; Ayatulloh Michael Musyaffi (Cogent Economics & Finance, 2023)
Equity-based financing (EBF) is an Islamic bank (IB) financing type that promotes justice, spirituality, and Islamic values. However, data shows that IBs still have low EBF. The researcher noted that with EBF, there is information asymmetry, agency problems and the potential for moral hazards, meaning EBF may be a risky type of transaction. This study aims to empirically show whether EBF is a risky transaction by looking at the role of EBF in non-performing financing (NPF), the z-score, and the return on average assets (ROAA). The research sample consisted of 54 IBs from 19 countries, with an observation period of 11 years (2009 to 2019). This study finds that EBF has a positive effect on NPF and does not affect the z-score and ROAA. The subsample test shows that EBF is riskier for large IBs than for small IBs. EBF has a positive effect on NPF and a negative one on ROAA for large IBs. In contrast, EBF has a negative effect on the z-score of small IBs. This research examines the robustness of these findings by employing other models as well as the generalised method of moment (GMM) to address any endogeneity problems.
Keywords: 330; fairness; monitoring costs; risk sharing; risky transactions